Money for the cause : a complete guide to event fundraising - Rosen, Rudolph A. (Rudolph Albert), 1952- (Conservation leadership series., 2012)
There has never been a greater need for raising the funds necessary to promote the causes that will help build a sustainable future. In Money for the Cause: A Complete Guide to Event Fundraising, veteran nonprofit executive director Rudolph A. Rosen lays out field-tested approaches that have been among those that helped him and the teams of volunteers and professionals he has worked with raise more than 3 billion for environmental conservation. As Rosen explains, fundraising events can range from elite, black-tie affairs in large cities to basement banquets a.